2016
DOI: 10.1097/j.pain.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Selective small molecule angiotensin II type 2 receptor antagonists for neuropathic pain

Abstract: Neuropathic pain affects up to 10% of the general population, but drug treatments recommended for the treatment of neuropathic pain are associated with modest efficacy and/or produce dose-limiting side effects. Hence, neuropathic pain is an unmet medical need. In the past 2 decades, research on the pathobiology of neuropathic pain has revealed many novel pain targets for use in analgesic drug discovery programs. However, these efforts have been largely unsuccessful as molecules that showed promising pain relie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…Prolonged exposure of Ang II (100 nM; 1h) did not elevate intracellular Ca 2+ ([Ca 2+ ] i ) in cultured mouse or human dorsal root ganglia (DRG) sensory neurons, irrespective of functional TRPA1 expression (Figure 5A, and Supplemental Figure 6 A and B), suggesting Ang II does not directly activate TRPA1 or other TRP channels in DRG neurons. Previous studies have reported that AT2R activation in mouse DRG neurons modulates TRPV1 function (4, 10). Intriguingly, in our experiments Ang II exposure did not influence the function of TRPA1 or TRPV1 channels in mouse or human DRG neurons (Figure 5 B and C).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Prolonged exposure of Ang II (100 nM; 1h) did not elevate intracellular Ca 2+ ([Ca 2+ ] i ) in cultured mouse or human dorsal root ganglia (DRG) sensory neurons, irrespective of functional TRPA1 expression (Figure 5A, and Supplemental Figure 6 A and B), suggesting Ang II does not directly activate TRPA1 or other TRP channels in DRG neurons. Previous studies have reported that AT2R activation in mouse DRG neurons modulates TRPV1 function (4, 10). Intriguingly, in our experiments Ang II exposure did not influence the function of TRPA1 or TRPV1 channels in mouse or human DRG neurons (Figure 5 B and C).…”
Section: Resultsmentioning
confidence: 97%
“…The lack of a precise mechanistic understanding has undoubtedly hampered the development of effective analgesics for neuropathic pain, which is poorly managed by existing drugs (2, 3). However, Angiotensin II (Ang II) type-2 receptor (AT2R) antagonists have recently proven efficacious in preclinical models of neuropathic and cancer pain (4), and the AT2R antagonist EMA401 has shown effective pain relief in PHN patients in phase II clinical trials (5). Importantly, the site of action for this antagonist remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no structural formula is disclosed. The AT2R antagonist EMA401, from Spinifex Pharmaceuticals Pty Ltd, Australia, and now acquired by Novartis, has been successfully tested in a phase II trial in patients with neuropathic pain …”
Section: Introductionmentioning
confidence: 99%
“…The AT2R antagonist EMA401, from Spinifex Pharmaceuticals Pty Ltd, Australia, and now acquired by Novartis, has been successfully tested in a phase II trial in patients with neuropathic pain. 61,62 The AT2R agonist C21 (8) has successfully passed safety Phase I in single and multiple ascending dose settings in healthy male volunteers and is now due for Phase II exploration, primarily in idiopathic pulmonary fibrosis (IPF). IPF has been chosen as primary indication because of the robust preclinical data on anti-fibrotic effects of C21 in various diseases models including not only pulmonary fibrosis 63 but also renal fibrosis, [64][65][66] vascular fibrosis, 67,68 and cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…administration of Ang II causes hypersensitivity (Shepherd, Copits, et al, ). While it was suggested that the induction of neuropathic pain involves the activation of AT2 receptors in DRGs (Smith et al, ), other reports indicate that it involves AT2 receptors on peripheral macrophages (Shepherd, Copits, et al, ; Shepherd, Mickle, et al, ). As the action site of Ang II is still debated and requires further studies, we have investigated pain transmission from the perspective of the spinal Ang system.…”
Section: Discussionmentioning
confidence: 99%